Un Siécle de Droit Médical en France (1902-2002) - Leca, Antoine (Victoria University of Wellington Law Review, 2004)
This article examines the doctrine of Droit des Patients (patients’ rights) in metropolitan France, outlines the historical development of the doctrine, and places it in its modern context. After discussing the emergence of patients’ rights, Professor Leca canvasses the various threads of reasoning that have contributed to these rights as they are expressed in the 21st century. He covers the development of public health and access to health-care ideas that dominated the area until the 20th century, and the modern influences of ideas on the dignity of the person and consumer rights that have contributed to the current legal status of the rights of the patient.